Study on inhibiting effects of melamine polyphosphate on pulverized coal explosion: Investigation from macro and micro perspectives - Lu, Kunlun; Jiang, Bingyou; Xiao, Yang; Luo, Zhenmin; Chen, Xiaokun; Zhao, Yang; Wang, Yuanyuan (Fuel (Guildford), 2024)
•Pulverized coal explosion was completely inhibited by MPP powder at ratio of 30 %.•Pm and (dP/dt)m were decreased with the addition mass of MPP powder increased.•Combustion heat released by mixtures of pulverized coal with MPP powder reduced.•MPP powder prevented free radicals from participating in coal dust explosion. Unintended release of pulverized coal could lead to an explosion, resulting in significant losses for employees and companies. It is crucial to research explosion prevention for related enterprises. The pulverized coal explosion inhibition was conducted by investigating explosion characteristic parameters, thermal analysis, and microscopic characteristics from macro and micro perspectives. The findings suggested that pulverized coal explosion could be effectively inhibited by melamine polyphosphate (MPP) powder at a ratio of 30 %. Specifically, when the concentration of pulverized coal was 300 g/m3, the optimal inhibiting concentration of MPP powder was 78.3 g/m3. Explosion pressure was positively correlated with heat release during the explosion process. As the concentration of MPP powder increased, both combustion rate and heat release gradually decreased, leading to a reduction in explosion pressure. Pulverized coal explosion led to a significant consumption of active free radicals. However, when MPP was added, free radicals concentration in products gradually increased and approached the original level. Physical inhibition was achieved by absorbing heat and diluting the mixture with inert substances. Chemical suppression mainly occurred through the consumption of key oxygen radicals by phosphorus-based compounds. The findings of this work introduce a novel concept for utilizing MPP powder as a suppressant and offers a fundamental experiment for pulverized coal explosion suppression technology.